MIDDLE SCHOOLS PSYCHOLOGICAL AND PEDAGOGICAL REQUIREMENTS FOR MULTIMEDIA ELECTRONIC LITERATURE CREATED FOR (Academia Science Repository, 2023)
Psychological and pedagogical requirements for multimedia electronic educational literature created for secondary schools are presented.